2006
DOI: 10.1038/sj.onc.1209768
|View full text |Cite
|
Sign up to set email alerts
|

ErbB4 (JM-b/CYT-1)-induced expression and phosphorylation of c-Jun is abrogated by human papillomavirus type 16 E5 protein

Abstract: Human papillomavirus type 16 E5 (HPV-16 E5) is a highly hydrophobic membrane protein with weak-transforming activity, which is associated with ErbB4 receptor in HPV-16-infected cervical lesions. Presently, we investigated the transforming mechanisms of E5 involving ErbB4 signaling. Firstly, we report a role for ErbB4 (JM-b/CYT-1) receptor that activates c-jun gene expression and phosphorylating at Ser63 and Ser73 of the c-Jun protein in ligand-independent and Ras-c-jun NH 2 -terminal kinase-dependent pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Importantly, since 16E5 has no innate enzymatic activity, its ability to alter cellular function most likely relies on its association with numerous proteins and/or lipid rafts [14] of the host cell. Documented intracellular binding targets for 16E5 include the 16kDa pore-forming subunit of the vacuolar H + -ATPase [10,15], the heavy chain of HLA type I [16] and ErbB4, a member of the epidermal growth factor (EGF) receptor family [17]. In this study we identify a new cellular target for 16E5, karyopherin β3 (KNβ3).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, since 16E5 has no innate enzymatic activity, its ability to alter cellular function most likely relies on its association with numerous proteins and/or lipid rafts [14] of the host cell. Documented intracellular binding targets for 16E5 include the 16kDa pore-forming subunit of the vacuolar H + -ATPase [10,15], the heavy chain of HLA type I [16] and ErbB4, a member of the epidermal growth factor (EGF) receptor family [17]. In this study we identify a new cellular target for 16E5, karyopherin β3 (KNβ3).…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenic activity not only of 16E5 but also of other E5 proteins encoded by different papillomaviruses appears to be correlated to their capacity to affect the function of receptor tyrosine kinases such as PDGFR (Petti et al, 1991;Talbert-Slagle and DiMaio, 2008), EGFR (Pim et al, 1992;Straight et al, 1993;Crusius et al, 1998;Pedroza-Saavedra et al, 2010), ErbB2 (Crusius et al, 1998) and ErbB4 (Chen et al, 2007). In the case of EGFR, 16E5 is able to alter the intracellular pathways mediating EGF signaling, such as extracellular signal-regulated kinase-1 and -2 (Crusius et al, 1997;Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…HPV-16 E5 protein stimulates cell growth by forming a complex with the epidermal growth factor receptor, ErbB4, platelet-derived growth factor receptor, and colony-stimulating factor 1 receptor (12,16,41,50). In vivo studies have demonstrated that E5 is expressed soon after infection.…”
mentioning
confidence: 99%
“…E6 and E7 expression has been found in cervical cancer cell lines and cancer biopsy specimens, and the two proteins play roles in malignant transformation. They are independently able to immortalize various human cell types in tissue culture, but the efficiency of transformation is increased when they are coexpressed (50).HPV-16 E5 protein stimulates cell growth by forming a complex with the epidermal growth factor receptor, ErbB4, platelet-derived growth factor receptor, and colony-stimulating factor 1 receptor (12,16,41,50). In vivo studies have demonstrated that E5 is expressed soon after infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation